Exploring knowledge, perception of risk and biosecurity practices among researchers in the UK: a quantitative survey - Shannon, Caitriona; Quinn, Claire Helen; Sutcliffe, Chloe; Stebbing, Paul D.; Dally, Thomas; Glover, Anita; Dunn, Alison M. (Springer, 2018)
Accidental introduction and/or spread of invasive non-native species (INNS) can result from a range of activities including agriculture, transport, trade and recreation. Researchers represent an important group of stakeholders who undertake activities in the field that could potentially facilitate the spread of INNS. Biosecurity is key to preventing the introduction and spread of INNS. Risk perceptions are a fundamental component in determining behaviour, so understanding how researchers perceive the risks associated with their activities can help us understand some of the drivers of biosecurity behaviour in the field. The aim of this study was to investigate researchers’ perceptions of risk in relation to their field activities and whether risk perceptions influenced behaviour. We gathered quantitative data on perceptions of risk and biosecurity practices using an online questionnaire. Only 35% of all respondents considered their field activities to pose some risk in terms of spreading INNS. Higher risk perception was found in those who undertook high risk activities or where INNS were known/expected to be present. However, whilst respondents with experience of INNS were more likely to report consciously employing biosecurity in the field, this did not translate into better actual biosecurity practices. Awareness of biosecurity campaigns did in fact increase perception of risk, perceived and actual biosecurity behaviour. However, there remains a disconnect between reported and actual biosecurity practices, including a lack of understanding about what constitutes good biosecurity practice. These findings should be used to improve targeted awareness raising campaigns and help create directed training on biosecurity practices.
Keywords: Biosecurity practices; Invasive alien species; Human behaviour; Fieldwork; Invasive non-native species; Research; Risk perception